Alley cropping affects perennial bioenergy crop root distribution, carbon, and nutrient stocks. (22nd August 2020) - Gamble, Joshua D.; Johnson, Gregg A.; Current, Dean A.; Wyse, Donald L.; Zamora, Diomides S.; Sheaffer, Craig C.
Abstract: This study quantified root biomass distribution; root accrual of C, N, P, and K; and changes in soil organic carbon (SOC) associated with alley‐cropped switchgrass ( Panicum virgatum L.), prairie cordgrass ( Spartina pectinata Bosc ex Link), intermediate wheatgrass [ Thinopyrum intermedium (Host) Barkworth and Dewey 'Rush'], and a native polyculture planted between rows of 'NM6' poplar ( Populus maximowiczii × P. nigra ) and 'Fish Creek' willow ( Salix purpurea ) at two Minnesota sites (Empire and Granada). After 4 yr since establishment, SOC declined at each site but was not influenced by species selection. NM6 poplar–prairie cordgrass systems had among the highest root biomass, C, and nutrient accrual, with up to 16.3 Mg root biomass, 7.0 Mg C, 175 kg N, 31 kg P, and 97 kg K ha −1 . Fine roots were the largest fraction of belowground biomass, although course roots were also a large fraction for poplar and prairie cordgrass. Tree roots extended to 6 m into the crop alley, although 85–89% were within 1 m of tree rows, depending on tree species. Crop fine root biomass was reduced up to 67% at 1 m from tree rows and 20% at 3.5 m and was up to 142% greater in willow than in poplar alleys. Total root C was predominated by poplars at Empire regardless of herbaceous crop type, whereas the proportions of tree and crop root C varied by crop at Granada. These results suggest that prairie cordgrass is well suited to alley cropping and that, due to the competitive ability of poplars, productivity, C sequestration, and nutrient accrual may be greater in willow systems in the long term.